Factors associated with diabetes self-care activities in patients with type 2 diabetes mellitus - Hisni, Dayan; Wowor, Tommy JF; Syamsiah, Siti; Lubis, Rosmawaty (KHD-Production, 2026)
The chronic nature of Type 2 diabetes mellitus (T2DM) necessitates management strategies beyond pharmacotherapy, specifically consistent self-care and family support. While self-care is critical for glycemic control, the influence of urban sociocultural and family dynamics remains underexplored. This study aimed to evaluate diabetes self-care levels and their associations with demographics, disease knowledge, and family support among adults. A STROBE-compliant cross-sectional study was conducted with 89 purposively sampled adults at a public health center. Instruments included the Diabetes Knowledge Questionnaire (DKQ-24), Family Support Scale (HDFSS), and Summary of Diabetes Self-Care Activities (SDSCA). Reliability was established (Cronbach's α = 0.73–0.96). Data were analyzed using the Mann-Whitney U test and Spearman's rho test. The mean SDSCA score was 71.4 (SD=13.7). Self-care behaviors were significantly associated with university education (p=0.048), disease duration ≥5 years (p=0.002), and older age (r=0.73, p<0.001). Diabetes knowledge (r=0.285, p=0.007) and family support (r=0.219, p=0.039) showed weaker, yet significant, positive correlations. No significant gender differences were observed (p=0.527). Age emerged as the strongest predictor of self-care. These findings highlight the need for age-stratified interventions that integrate family support to optimize T2DM management.